Estresse prolongado único-emocional induz distúrbio gastrointestinal funcional: um modelo de interação cérebro-intestino - Marques, Luiza Souza (2022)
Currently, about 90% of the world’s population suffers from some degree of stress, making it an inevitability (WHO). It is known that excessive stress can precipitate psychopathologies, such as depression and anxiety, and alter gastrointestinal functionality and microbiota. Consequently, favoring the development of functional gastrointestinal disorders (FGIDs), which are defined by deregulation in the brain-gut interaction. In this context, animal models of stress become a tool useful to elucidate the mechanisms involved in this interaction. However, most FGIDs models are chronic or have limited validity. Therefore, this study aimed to investigate whether a model of emotional stress induces FGID, through bidirectional braingut interaction mediated by depressive/anxious-like phenotype, intestinal dysfunction, and modulation of intestinal bacterial microbiota in adult male Swiss mice. This study was approved by the UFSM Ethics Committee on the use of animals under number # 1535120320. First, the animals were divided into two groups [Control and Emotional-Single Prolonged Stress (ESPS)], mice in the E-SPS group were subjected to a single sequential exposure to three stressors: immobilization (2h), forced swimming (15min), followed by recovery (15min), and finally exposure to predator odor (3min). After 7 days (incubation period), the animals were evaluated in behavioral tests predictive of depression and anxiety. The parameters, the number of fecal pellets and fecal moisture content (%), were determined. After 24h, samples of stool, blood, and colon tissue were collected for analysis. The results showed depressive- and anxious-like phenotypes in animals subjected to the E-SPS demonstrated in tests predictive of depression (tail suspension test, forced swimming, and splash test) and anxiety (elevated plus maze test), suggesting the brain-gut interaction. E-SPS mice had the intestinal functionality altered, increased intestinal transit, number of fecal pellets and, fecal moisture content, and increased intestinal permeability, associated with a decrease in epithelial junction proteins, significantly Claudin-1. Furthermore, exposure to E-SPS modulated the profile and diversity of the intestinal microbiota of the animals when compared to the non-stressed group. Specifically, a decrease in the relative abundance of the phylum Bacteroidetes, class Bacteroidia, order Bacteroidales, family Muribaculaceae and Prophyromonadaceae, as well as an increase in the phyla Firmicutes and Actinobacteria, order Coriobacteriales, and the Firmicutes/Bacteroidetes ratio and the presence of the genus Mucispirillum. Taken together, the results demonstrated that the E-SPS model induced FGID, through the brain-gut interaction, mediated by behavioral changes, intestinal dysfunction, and modulation of the intestinal bacterial microbiota in male Swiss mice.